THE SEMANTIC FEATURE ANALYSIS ON TEACHING VOCABULARY FOR YOUNG LEARNERS - Dieni Nurhasanah Dwihastuti (Lingua, 2022)
ABSTRACT As vocabulary is a necessary mode of communication, it must be acquired first to be able to master the English language. It is a good idea to start vocabulary classes in elementary school. As their memory is still strong in remembering things, they are ready to learn anything new. However, since English is a second language, teachers will need to employ strategies to have students acquire and memorize new words. This study focuses on linguistic knowledge, that is, semantics, which the teacher uses in the classroom and the learning materials to encourage students’ vocabulary. This is a content analysis of the teacher's approaches to teaching new words to young learners using semantic aspects. This research will be observed through two videos of English-language classrooms. The findings reveal that semantic features such as synonym and antonym pairs, polysemy, and applying in short sentences were used in the classroom when teaching vocabulary. During the class, photos, cassettes, music, and a variety of other learning resources are used. These strategies motivate and encourage students to learn the new vocabulary. Keywords: vocabulary, instruction, young learner, semantics